2021
DOI: 10.2147/opth.s305717
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Efficacy and Safety of Mycophenolate Mofetil in Active Moderate-to-Sight-Threatening Thyroid Eye Disease

Abstract: Purpose: There is no universal consensus on second-line agents for the treatment of moderate/severe to sight-threatening thyroid eye disease (TED) to maintain remission after first-line intravenous methylprednisolone (IVMP). This study investigates the efficacy and safety of mycophenolate mofetil (MMF) in TED patients in a real-world setting and over a longer period than previous randomized controlled trials. Methods: A retrospective cohort study of TED patients with active moderate/severe to sight-threatening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
3
11
0
2
Order By: Relevance
“…Despite these studies and according to Jiskra, the effects of biologic drugs such as MMF and cyclosporine in TED patients have not been adequately studied, and there is a controversy about their use in the treatment (17). This prospective interventional case series showed that MMF plus low-dose oral prednisolone as a new treatment regimen was significantly effective in 94.2% of patients, consistent with data previously reported on the effect of MMF on moderate to severe GO (16,(18)(19)(20)(21). Similar to the results of teprotumumab (novel insulin-like growth factor I receptor antibody) in active TED (22,23), as expected, MMF plus low-dose oral prednisolone showed the greatest effectiveness on CAS, proptosis and diplopia, and this factor significantly decreased during the study, and this decrease occurred earlier in CAS than proptosis and diplopia, suggesting that; MMF like teprotumumab was more efficient than corticosteroids in controlling local inflammation.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Despite these studies and according to Jiskra, the effects of biologic drugs such as MMF and cyclosporine in TED patients have not been adequately studied, and there is a controversy about their use in the treatment (17). This prospective interventional case series showed that MMF plus low-dose oral prednisolone as a new treatment regimen was significantly effective in 94.2% of patients, consistent with data previously reported on the effect of MMF on moderate to severe GO (16,(18)(19)(20)(21). Similar to the results of teprotumumab (novel insulin-like growth factor I receptor antibody) in active TED (22,23), as expected, MMF plus low-dose oral prednisolone showed the greatest effectiveness on CAS, proptosis and diplopia, and this factor significantly decreased during the study, and this decrease occurred earlier in CAS than proptosis and diplopia, suggesting that; MMF like teprotumumab was more efficient than corticosteroids in controlling local inflammation.…”
Section: Discussionsupporting
confidence: 84%
“…The MMF dosage that was initially used in combination with low-dose prednisolone, according to the study design, was based on a previous work in autoimmunity (24)(25)(26). A previous study showed that even low doses of MMF (1,000 mg/d) were effective in suppressing orbital inflammation (16)(17)(18)(19)(20)(21). However, in our study, to better respond to MMF, we added the lowest dose of corticosteroids (oral prednisolone, 5 mg/d) to the treatment regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Riedl et al analyzed the AEs of moderate-dose MMF in GO patients, and the results showed that MMF was well tolerated [ 31 ]. Currently, MMF is mostly used to treat patients with active moderate-to-severe GO who are resistant to GC, and some studies indicate that MMF is safe and effective as a second-line immunosuppressant [ 32 , 33 ]. The 2021 EUGOGO recommended intravenous MP in combination with MMF as a first-line treatment, taking all factors into account.…”
Section: Discussionmentioning
confidence: 99%
“…2020; Quah Qin Xian et al. 2021). Rituximab is a monoclonal antibody directed against CD20, which has been used successfully to treat active, moderate‐to‐severe GO since 2006 (Salvi et al.…”
Section: Discussionmentioning
confidence: 99%